Laser Photobiomodulation 808 nm: Effects on Gene Expression in Inflammatory and Osteogenic Biomarkers in Human Dental Pulp Stem Cells - Rocha, Elaine A. da; Alvarez, Marcela M. P.; Pelosine, Agatha M.; Carrilho, Marcela Rocha O.; Tersariol, Ivarne L. S.; Nascimento, Fábio D. (Frontiers in Pharmacology, 2022)
The tissue engineering of dental oral tissue is tackling significant advances and the use of stem cells promises to boost the therapeutical approaches of regenerative dentistry. Despite advances in this field, the literature is still scarce regarding the modulatory effect of laser photobiomodulation (PBM) on genes related to inflammation and osteogenesis in Postnatal Human Dental Pulp Stem cells (DPSCs). This study pointedly investigated the effect of PBM treatment in proliferation, growth and differentiation factors, mineralization, and extracellular matrix remodeling genes in DPSCs. Freshly extracted human third molars were used as a source for DPSCs isolation. The isolated DPSCs were stimulated to an inflammatory state, using a lipopolysaccharide (LPS) model, and then subjected or not to laser PBM. Each experiment was statistically evaluated according to the sample distribution. A total of 85 genes related to inflammation and osteogenesis were evaluated regarding their expression by RT-PCR. Laser PBM therapy has shown to modulate several genes expression in DPSCs. PBM suppressed the expression of inflammatory gene TNF and RANKL and downregulated the gene expression for VDR and proteolytic enzymes cathepsin K, MMP-8 and MMP-9. Modulation of gene expression for proteinase-activated receptors (PARs) following PBM varied among different PARs. As expected, PBM blocked the odontoblastic differentiation of DPSCs when subjected to LPS model. Conversely, PBM has preserved the odontogenic potential of DPSCs by increasing the expression of TWIST-1/RUNEX-2/ALP signaling axis. PBM therapy notably played a role in the DPSCs genes expression that mediate inflammation process and tissue mineralization. The present data opens a new perspective for PBM therapy in mineralized dental tissue physiology.